Youth Soccer Parents' Perceptions of Long-Term Effects of Concussion . Issue 3 (2nd April 2020) - Schatz, Philip; Corcoran, Mary; Kontos, Anthony P.; Elbin, RJ
ABSTRACT: Increased focus on sports-related concussion (SRC) in football in the media, and mandatory concussion education for parents of youth sport athletes, may result in parental concern that youth athletes will experience long-term effects from concussion. We sought to identify beliefs about long-term effects of concussion in parents of youth soccer athletes. Four hundred and eleven parents from soccer leagues in three states completed a survey assessing parents' perceptions and knowledge of long-term effects of SRC. Nearly all youth soccer parents surveyed (96.5%) believe there are long-term effects from SRCs, 76% reported concern their child would sustain a concussion, and 71% had talked with their child about concussion symptoms/reporting. Parents ranked tackle football as having the highest risk for concussion, followed by soccer, ice hockey, cheerleading, and lacrosse. Parents of children that had previously sustained a concussion were 8.3x more likely to be concerned their child would sustain a concussion, and parents with a personal history of concussion were 2x more likely to consider not allowing their child to participate in youth sports. There are wide-spread beliefs among youth soccer parents regarding long-term effects of SRCs, and concerns their children will sustain concussions while participating in youth sports.